Ethics in human-robot interaction research - Moreno, Robinson Jimenez; Espitia Cubillos, Anny Astrid; Martinez Baquero, Javier Eduardo (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
This paper explores the basic ethical and bioethical considerations necessary to mediate interaction with various everyday robots, analyzing several stateof-the-art reports and own research, considering advances in human-robot interaction (HRI) and artificial intelligence (AI). It is important to indicate that the adoption of robotic assistance systems is limited by users' nervousness about the enforcement of ethics, security and privacy of their information, in addition to the regular threats of Internet use, considering that HRI must reason its social and ethical impacts by including specific issues associated with HRI such as autonomy, transparency, deception and policies. In this way, it is relevant both to evaluate how robotic architectures influence people's daily lives and to study how to avoid possible negative impacts. Finally, it is significant to establish the ethical considerations required to enable the development of AI algorithms that help HRI in a natural way.